Neuropsychological performance in patients with focal drug-resistant epilepsy and different factors that affect their performance - Nirmeen A. Kishk; Marwa Farghaly; Amani Nawito; Reham Mohamed Shamloul; Mona K. Moawad (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery, 2022)
Abstract Background Drug-resistant epilepsy (DRE) accounts for nearly 30% of patients with epilepsy, which is associated with high incidence of cognitive comorbidity. The aim of this work was to study the role of neuropsychological assessment in patients with epilepsy, and different factors that affect their performance in patients with multiple factors (focal onset DRE). Methods 118 patients were recruited from Kasr Alainy hospital, epilepsy outpatient clinic with focal DRE. The patients’ demographic and clinical data were collected, Electroencephalograph (EEG) interictal/ictal (when available), and brain imaging (MRI epilepsy protocol). Neuropsychological assessment by Wechsler Adult Intelligence Scale (WAIS-IV), proposed neurocognitive assessment battery and mood assessment was done. Their performance in neuropsychological assessment was correlated with the collected data. Concordance between different assessment modalities and brain lesion were done. Results Among recruited patients, 67.3% of patients showed Full-scale Intelligence Quotient (FSIQ) was less than average. FSIQ score significantly correlated with years of education, and number of anti-seizure medications (ASMs). Neurocognitive assessment battery could achieve cognitive profile of the patients but with poor lateralizing value. Executive function was the most affected cognitive domain. History of status epilepticus significantly affect FSIQ and executive function performance. Fifty-six percent of patients had depression. Among the analyzed factors, FSIQ and lesional brain imaging significantly affected neurocognitive performance of studied patients. Clinical semiology had better concordance in lateralization (74.7%) and localization (69.5%) with brain imaging compared to ictal EEG. Among patients who had ictal EEG recording, 36.4% patients (25% were temporal lobe) had complete concordance, while 38.6% patients had partial concordance. Conclusions Among analyzed factors, FSIQ was the most significant determinant of studied population’s neurocognitive performance. Clinical semiology were the best correlated with brain lesion. Complete concordance was best detected at the temporal lobe.